Enhancing Executive Functions and Handwriting with a Concentrative Coordination Exercise in Children with ADHD: A Randomized Clinical Trial. Issue 4 (August 2022) - Chang, Shao-Hsia; Shie, Jung-Jiun; Yu, Nan-Ying
Handwriting difficulties are common in children with Attention-Deficit/Hyperactivity Disorder (ADHD), and they have been associated with lower academic achievement and self-esteem. Our aim in this study was to determine if training coordination of the head, eyes, and arm and engaging in the necessary visual concentration associated with table tennis would improve executive functions and school-based handwriting among children with ADHD. We designed a randomized controlled trial to explore the therapeutic efficacy of this table tennis training and recruited 48 children with ADHD that we randomly assigned to one of three equal-sized training groups: (a) actual table tennis, (b) simulated table tennis (exergame), or (c) a control group receiving no additional training. The training intervention lasted 12-weeks in which the two different table tennis trainings (i.e., actual or simulated) were scheduled for three one-hour sessions per week. Outcome measures included a computerized handwriting evaluation, the Stroop test, and the Wisconsin Card Sorting Test (WCST). Participants in each table tennis training group showed significant improvements in handwriting performance, response time, and required time to achieve automation. Both intervention groups also showed significant improvements on the Stroop Color-Word test, but only the actual table tennis training group showed a significant improvement on the WCST. This study provided evidence of at least short-term improvements in executive functions and handwriting problems in children with ADHD through their participation in table tennis motor coordination activities.